Effect of Manganese on Co–Mn/CNT Bimetallic Catalyst Performance in Fischer–Tropsch Reaction - Akbarzadeh, Omid; Mohd Zabidi, Noor Asmawati; Aljunid Merican, Zulkifli Merican; Sagadevan, Suresh; Kordijazi, Amir; Das, Sourav; Babadi, Arman Amani; Rahman, Marlinda Ab; Hamizi, Nor Aliya; Wahab, Yasmin Abdul; Johan, Mohd Rafie (MDPI, 2019)
Cobalt (Co) catalyst is supported by carbon nanotubes (CNT) using a strong electrostatic adsorption (SEA) method. To promote activity and selectivity as well as find the optimum loading percentage and its effect on catalyst performance, manganese (Mn) has been added to the Co/CNT catalyst. Samples were characterized by a scanning electron microscope (SEM-EDX), transmission electron microscope (TEM), hydrogen temperature programmed reduction (H2-TPR), Zeta potential, Brunauer-Emmett-Teller (BET) analysis, X-ray diffraction (XRD), and X-ray spectroscopy (XPS). TEM images illustrated an intake of metal particles which were highly dispersed, having a narrow particle size distribution of 6-8 nm to the external and internal CNT support. H2-TPR showed a lower temperature reduction with Mn at 420 °C for Fischer-Tropsch synthesis (FTS) reaction. The Co-Mn/CNT catalyst performance test for FTS was performed at a temperature of 240 °C in a fixed-bed micro-reactor at a pressure of 2.0 MPa. The addition of manganese resulted in a lower methane selectivity and a higher C5+ product with an optimum percentage of 5% of manganese. CO conversion was 86.6% and had a C5+ selectivity of 81.5%, which was higher than the catalysts obtained using only Co on pretreated CNT. © 2019 by the authors.